Avaliação de híbridos de milho visando à biofortificação com zinco - Gonçalves, Ana Stella Freire (2017)
Human malnutrition by zinc (Zn) is a growing concern in the contemporary setting. Classified among the most serious micronutrient deficiencies, especially in developing countries, it is considered a major cause of child mortality. Cereals such as maize (Zea mays L.) stand out as a source of food in these countries, however it presents a low Zn concentration, which it does not contribute to minimize the deficiency in humans. In view of this situation, biofortification may become a promising technique, in order to increase the selected micronutrient content in basic foods, improving their nutritional quality. In this context, this study selected hybrids of maize that are on the market, aiming biofortification with the micronutrient Zn, by means the management of foliar fertilization. The concentration of Zn in the grains was quantified in field experiments during two growing seasons by means of acid digestion followed by atomic absorption spectrophotometer analysis. The results provided information for the genotypes selection with higher Zn uptake potential, aiming the food security of the population, especially in the low income population. In general, for the different doses applied, within the same growing season, hybrids presented the highest Zn concentrations in grains when the highest dose of sulfate (10g L-1 ) was applied, reaching average concentrations up to 24.48mg Kg-1 , except for the hybrid RB9077, which reached 27.62mg kg-1 , when 5g L -1 of sulfate was applied in the second growing season. Although the averages presented by the hybrids for the Zn concentration in the grains are below the target value (40 mg kg-1 ) established by the Harvest Plus program, studies report that the Zn application at later stages of the crop can be a responsive alternative, resulting in a greater translocation of the nutrient to the grains, placing the greater demand during the filling phase of the grains.